REKONSTRUKSI MODEL PUTUSAN HAKIM PERKARA KDRT MELALUI PENDEKATAN HUKUM PROGRESIF - Lucky Endrawati; Nurini Aprilianda; Mufatikhatul Farikha (Jurnal Media Hukum, 2015)
Case of domestic violence had increased every year, this is caused by people have a paradigm that domestic violence is privat domain. Even though, domestic violence be regulated by domestic violence elimination Act number 23 in 2004, but the victim often don’t recognize justice. In common law jurisdictions concentrate on judges, whose opinions contain masses of reasoning. In civil law jurisdictions, they focus more on the writings of jurists, both because their works are regarded as important evidence of what the law is, and because court judgements are much less elaborate in their ratiocinations, judge legal reasoning used Act priority, specially Act for Domestic Violence Elimination. So, that reasons for use progressive law approach